Peran moderasi literasi keuangan dalam hubungan antara adopsi fintech dan kinerja keuangan UMKM di kota Ambon - Patty, Martha Racwel; Rumtutuly, Hansen Hein (Indonesian Indovisi Institute, 2024)
This study aims to examine the influence of financial technology (fintech) adoption on the financial performance of micro, small, and medium enterprises (MSMEs) in Ambon City, with financial literacy serving as a moderating variable. A quantitative approach was applied using a survey method involving 83 MSME owners who have utilized fintech services in their business operations. Data analysis was carried out using SmartPls through the assessment of the outer and inner models. The findings reveal that fintech adoption has a positive and significant effect on MSME financial performance. This suggests that the use of fintech enhances operational efficiency, expands access to financial services, and accelerates transaction processes. Moreover, financial literacy was found to strengthen the relationship between fintech adoption and financial performance, indicating that MSMEs with higher levels of financial literacy are better able to optimize the use of financial technology to improve their business outcomes. The study contributes to the advancement of digital financial management literature and provides practical implications for improving financial literacy and promoting MSME digitalization in island-based regions.